Johor Land Berhad Pasir Gudang Division / Nadia Jamilah Jamaluddin - Jamaluddin, Nadia Nabilah (2017)
In order to complete the graduation requirement, trainee needs to undergo eight weeks of industrial training in qualify company. Trainee starts their industrial training from 18th April 2017 until 11th June 2017. The company that has been selected by trainee is Johor Land Berhad Pasir Gudang Division. There are several sections under JLand; every section has their own specialty, with interest task and function. During training, we get to learn important task at the branch. Besides that, trainee also get to attend site visit, deals with construction drawing, learn to improve communication skills, get involve with office activity, learn to be more discipline and punctual. Last but not least, industrial training is the best method in order to expose student to the real working environment and for preparation for student to be a good engineer in the future.